3D-Printable Gelatin Methacrylate-Xanthan Gum Hydrogel Bioink Enabling Human Induced Pluripotent Stem Cell Differentiation into Cardiomyocytes - Virginia Deidda; Isabel Ventisette; Marianna Langione; Lucrezia Giammarino; Josè Manuel Pioner; Caterina Credi; Federico Carpi (Journal of Functional Biomaterials)
We describe the development of a bioink to bioprint human induced pluripotent stem cells (hiPSCs) for possible cardiac tissue engineering using a gelatin methacrylate (GelMA)-based hydrogel. While previous studies have shown that GelMA at a low concentration (5% w/v) allows for the growth of diverse cells, its 3D printability has been found to be limited by its low viscosity. To overcome that drawback, making the hydrogel both compatible with hiPSCs and 3D-printable, we developed an extrudable GelMA-based bioink by adding xanthan gum (XG). The GelMA-XG composite hydrogel had an elastic modulus (~9 kPa) comparable to that of cardiac tissue, and enabled 3D printing with high values of printing accuracy (83%) and printability (0.98). Tests with hiPSCs showed the hydrogel’s ability to promote their proliferation within both 2D and 3D cell cultures. The tests also showed that hiPSCs inside hemispheres of the hydrogel were able to differentiate into cardiomyocytes, capable of spontaneous contractions (average frequency of ~0.5 Hz and amplitude of ~2%). Furthermore, bioprinting tests proved the possibility of fabricating 3D constructs of the hiPSC-laden hydrogel, with well-defined line widths (~800 μm).